PSYCHOLOGICAL WELL BEING AND ADJUSTMENT OF SINGLE PARENTS: PSYCHOSOCIALAND ECONOMIC CHALLENGES - Amina Hanif Tarar (Army Medical College Rawalpindi, 2021)
Objective: To explore the relationship between psychological well-being and psycho-social adjustment of economically independent and dependent single parents belonging to various socio-economic classes.